Development and characterization of intraspecific hybrids derived from Cucumis melo L. (Bangladesh Journal of Botany, 2019)
An intraspecific hybridization programme among Cucumis species involving eight genetically diverse parents of C. melo L. varietal group viz., IC-0599709, Punjab Sunehri, Pusa Madhuras, Kashi Madhu (C. melo L.), AHK-119 (C. melo var. callosus), AHLM-2 (C. melo var. utilissimus), AHS-82 (C. melo var. momordica) and Arya-1 (C. melo var. chate) were undertaken. Among the dessertic F1 hybrids, IC-0599709 × Punjab Sunehri resulted best with respect to first fruit harvest (73.33 days), fruit weight (938.00 g), fruit diameter (11.90 cm), flesh thickness (3.07 cm), total soluble solids (9.73%) and flesh colour (salmon orange). F2 population of AHK-119 × Kashi Madhu produced maximum number of marketable fruits per plant (11.2) weighing 350.00 g in 86.1 days. It was also found to be tolerant to high temperature. The F2 population of AHK-119 × Kashi Madhu were found to be tolerant to high temperature. The existing variability among the parents, intra-specific crosses and segregating generations for fruit (size, shape, colour), yield and quality parameters could be exploited to develop new segregants with desirable traits.